Prevalence of Dyslipidemia and Associated Factors among the Sub-Urban Bangladeshi Population - Islam, Nadira; Rahman, Md Zillur; Choudhury, Sadia; Afrin, Lazina; Rahman, Sonia; Aftabuddin, Mohammad (University Heart Journal, 2012)
Dyslipidemia is highly prevalent in the urban and rural areas of Bangladesh but information in the suburban, is limited. The objective of this study was to determine the prevalence of dyslipidemia in sample population who live in the sub-urban area of Bangladesh. Random sampling of the volunteers aged > or = 18 years in Bhaluka upozilla of Mymensingh district was done. After 12-hour fasting, the blood sampling was drawn for the analysis of fasting glucose, total cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol and low-density lipoprotein (LDL) cholesterol. In the present study, we have shown that there is increasing trend of dyslipidemia even in the sub-urban community. Women had significantly higher body mass index, serum cholesterol and LDL cholesterol levels than men after 40 years of age. Of the study population 16.9% had high TC (e240 m/dl), and 8.8% had low HDL-C (d40 mg/dl). The population with high (e160 mg/dl) LDL-C was 15.7%. In addition, 17.8% had high TG (e200 mg/dl) and 2.0% had very high TG (e350 mg/dl). Our findings also suggest a protective role of ordinary Bangladeshi diet such as fish cooked in mustard oil on dyslipidemia. Individually, both fish and the mustard oil are rich in unsaturated fatty acids, and biologically, their beneficial effects are related not only to reduction of blood pressure, but also to lowering of lipids and to their antithrombotic effects. In conclusion, prevalence of dyslipidemia was very high in Bangladeshi sub-urban region. Useful role of fish cooked in mustard oil, as a protective factor needs to be probed further in future longitudinal studies. The observed prevalence of dyslipidemia in this study suggests the need for a comprehensive national policy to control dyslipidemia in Bangladesh. Further surveillance in this population is essential in verifying the impact of dyslipidemia as a risk of cardiovascular disease in Bangladeshi people. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11662 University Heart Journal Vol. 8, No. 1, January 2012